Do summary care records have the potential to do more harm than good? Yes. (16th June 2010) - Anderson, Ross
Abstract : Ross Anderson argues that the national electronic database of patient records is not fit for purpose and illegal, but Mark Walport (doi:10.1136/bmj.c3022 ) believes that it will make valuable contributions to better care